2018
DOI: 10.1037/sgd0000263
|View full text |Cite
|
Sign up to set email alerts
|

Internalized heterosexism and posttraumatic stress disorder symptoms: The mediating role of shame proneness among trauma-exposed sexual minority women.

Abstract: Sexual minority women are more likely to experience negative mental health outcomes, including posttraumatic stress disorder (PTSD), than heterosexual women. Meyer’s (2003) minority-stress theory posits that this elevated risk of psychopathology results from stressors specific to the experience of holding a minority identity, and Hatzenbuehler (2009) suggested that these effects may be mediated by general psychological risk factors. Internalized heterosexism is conceptually and empirically linked to shame pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 57 publications
2
23
2
Order By: Relevance
“…A forest plot of the associations between shame and PTSD symptoms for all studies can be found in Figure 2. From this plot, three effect sizes were identified as statistical outliers (Babcock Fenerci & DePrince, 2018;Lancaster & Erbes, 2017;Straub et al, 2018). The results of analysis of the heterogeneity of variance were nonsignificant, Q(24) = 18.23, p = .792, I 2 = 0.00%, 95% CI [0.00%, 31.91%], indicating minimal betweenstudy variance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A forest plot of the associations between shame and PTSD symptoms for all studies can be found in Figure 2. From this plot, three effect sizes were identified as statistical outliers (Babcock Fenerci & DePrince, 2018;Lancaster & Erbes, 2017;Straub et al, 2018). The results of analysis of the heterogeneity of variance were nonsignificant, Q(24) = 18.23, p = .792, I 2 = 0.00%, 95% CI [0.00%, 31.91%], indicating minimal betweenstudy variance.…”
Section: Resultsmentioning
confidence: 99%
“…We used the effect size for the overall scale if effect sizes for multiple subscales were reported (Harman & Lee, ). Averages were calculated for studies that reported more than one shame outcome (Dorahy et al., ) or on multiple shame subscales without a total score (Neufeld, Sikkema, Lee, Kochman, & Hansen, ; Straub, McConnell, & Messman‐Moore, ; Zerach & Levi‐Belz, ). Borenstein, Hedges, Higgins, and Rothstein () suggest the weighting of average effect sizes; however, recent work has shown that this may create potential bias by introducing a third, confounding variable in a random‐effects meta‐analysis (Shuster, ).…”
Section: Methodsmentioning
confidence: 99%
“…This may be mediated by the internalization of stigma. According to minority stress theory (Meyer, 2003), internalized homophobia/transphobia is predictive of various forms of psychopathology, including PTSD symptoms, psychological distress, and substance abuse (Puckett & Levitt, 2015;Puckett, Mereish, Levitt, Horne, & Hayes-Skelton, 2018;Straub, McConnell, & Messman-Moore, 2018).…”
Section: Stressors and Ptsd In Marginalized Communitiesmentioning
confidence: 99%
“…Adequate internal reliability (Cronbach’s α = .82) has been reported for scores on the IHP-R in LGBQ adult samples (Herek et al, 2009). Further, the IHP-R has been used as a measure of internalized heterosexism with bisexual women (e.g., Straub et al, 2018) and validity of scale scores has been supported by positive associations with identity concealment and expectations of rejection among sexual minority women (Mason & Lewis, 2015). A mean score for 5 items is calculated, where higher scores indicate greater levels of internalized heterosexism.…”
Section: Methodsmentioning
confidence: 99%